Cereal chemistry. - American Association of Cereal Chemists (St. Paul, Minn. : American Association of Cereal Chemists)
Includes papers delivered at annual meetings of the American Associa tion of Cereal Chemists.
Chemical abstracts
Vols. 1-10, 1924-33, with v. 10; Vols. 11-20, 1934-43 (suppl. to v. 22, no. 2). 1 v.; Vols. 21-30, 1944-53. 1 v.; Vols. 31-40, 1954-63. 1 v .
Abstracts and indexes for 1960-<1992> are available on a computer di sk product called: Cereal source.
Keywords: Chemistry, Technical -- Periodicals; Baking -- Periodicals; Cereals -- Periodicals; Food Analysis -- Periodicals